PENGATURAN HAK-HAK TERSANGKA/ TERDAKWA DALAM HUKUM ACARA PIDANA SEBAGAI JAMINAN HAK-HAK ASASI MANUSIA DAN WARGANEGARA - Yuliandari, Erna (PKn Progresif, 2007)
In life of society often happened doing an injustice resulting annoyed of peacefulness and security. Regulation-regulation intend to be created to reliaze peacefulness of sociental life in order to going to secure and prosperous and fair society. Essence and intention is existence of law orders is to give justice guarantee and to be guaranteed by right as human being and obligations for every its citizen, that is one side have same in law and on the other side also abliged to respect law.